ISOLATION AND IDENTIFICATION OF ARBUSCULAR MYCORRHIZAL FUNGI (AMF) IN CASHEW PLANTS (Anacardium occindentale L.) IN DATAH VILLAGE, ABANG DISTRICT OF KARANGASEM REGENCY - I Ketut Suada; Evy Prima; Made Sritamin; I Wayan Adiartayasa; I Gede Ketut Susrama; I Gede Putu Wirawan (International Journal of Biosciences and Biotechnology, 2018)
Isolation and identification of arbuscular mycorrhizal fungi (AMF) in cashew plants was carried out in Datah Village, Abang District of Karangasem Regency. This study aims to determine the diversity of mycorrhizal spores in the cashew rhizosphere and AMF infections in the roots of cashew plants. The result in microscopic observations found 5 genera of AMF spores such as Glomus, Racocetra, Entrophospora, Septoglomus, and Acaulospora and the population of the genus Glomus were found most dominant in the rhizosphere of cashew plants. The result of staining root with trypan blue obtained the internal structure of AMF in the form of vesicles, arbuscules and hyphae found in root tissue of cashew plants. The result of AMF DNA amplification with primer NS31 and AML2 showed 560 bp bands in electrophoresis with 1% agarose gel determined AMF infection in root of cashew plants.